MENINGKATKAN KEMAMPUAN CALISTUNG ANAK TUNAGRAHITA DENGAN METODE VAKT (VISUAL, AUDIO, KINESTETIK, DAN TAKTIL) - Novita Tri Jayanti; Wiwien Dinar Pratisti (Jurnal Muara Pendidikan, 2023)
Education is very important in the life of citizens and includes children with special needs which are also regulated by the state. According to the law, children with special needs have the right to get a quality education. Children with mental retardation, in learning to read, write, and count, of course, face obstacles in their cognition, mastery, use of language, and physical-motor abilities. Therefore they need learning methods to improve their cognitive. The purpose of this article review is to review scientific articles that discuss effective scientific methods for mentally retarded children. The method used is library research with reference sources obtained from Google Scholar. The criteria for articles used as references are journals published in the last 10 years from 2012-2021. The results of the selected review articles state that visual, audio, kinesthetic, and tactile methods can be applied as learning methods for mentally retarded children, by optimizing all sensory functions. The application of this method is considered effective for helping mentally retarded children in the learning process, especially in reading, writing, and arithmetic. With this, it is hoped that it can help improve the learning achievement of mentally retarded children.